ANALISIS PENETAPAN HARGA PRODUK SAYURAN HIDROPONIK PADA ANDRI FARM DI KECAMATAN LUWUK SELATAN KABUPATEN BANGGAI - Ismail Djamaluddin; Dian Puspapratiwi; Ahmad Rifaldi (Fakultas Pertanian Universitas Tompotika Luwuk, 2023)
Product pricing is the value of a product that has been determined by the company to be paid by consumers in obtaining the desired product. The purpose of this study is to find out how to determine the selling price of products. This research has been carried out at Andri Farm Hydroponics, South Luwuk District. The study was conducted from August to September 2022 using quantitative descriptive data analysis methods, where the full costing method to calculate the cost of goods produced and the cost-plus pricing method to determine selling prices to consumers. The selling price according to Andri Farm Hydroponics for lettuce, kale, caisim, and pakcoy vegetables is IDR 6,000, while according to the calculation of the selling price of the cost plus pricing method for lettuce vegetables is IDR 2,718.83, for kale vegetables is IDR 5,723.50, for caisim vegetables is IDR 3,914.07, and for pokcoy vegetables is IDR 3,311.37. So that the results based on the full costing component of the selling price set by the company are higher than the selling price calculated based on the Cost Plus Pricing method. This means that the determination of the selling price of Andri Farm Hydroponic vegetables in South Luwuk District, Banggai Regency has been met from the minimum profit standard.